1999
DOI: 10.1074/jbc.274.20.13847
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of α-Helical Coiled-coil Dimerization in Chicken Skeletal Muscle Light Meromyosin

Abstract: The dimerization specificity of the light meromyosin (LMM) domain of chicken neonatal and adult myosin isoforms was analyzed by metal chelation chromatography. Our results show that neonatal and adult LMMs associate preferentially, although not exclusively, as homodimeric coiled-coils. Using chimeric LMM constructs combining neonatal and adult sequences, we observed that a stretch of 183 amino acids of sequence identity at the N terminus of the LMM was sufficient to allow the adult LMM to dimerize in a non-sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 44 publications
1
8
1
Order By: Relevance
“…Homodimeric myosins are also preferentially formed in invertebrates such as Caenorhabditis elegans ( Miller et al, 1983 ) and in vertebrate skeletal muscles, where different developmental heavy chain isoforms are the products of separate genes in the multinucleated cells ( Lowey et al, 1991 ). When bacterially expressed LMM fragments of the adult and neonatal isoforms were denatured and renatured in vitro, they preferentially formed homodimers, indicating that the information for skeletal myosin formation probably is inherent in the amino acid sequence ( Arrizubieta and Bandman, 1999 ). In contrast, mammalian cardiac muscle contains amounts of heterodimeric V2 myosin comparable to those of the homodimeric V1 and V3 forms during certain stages of development ( Hoh et al, 1978 ; Lompre et al, 1979 ).…”
Section: Discussionmentioning
confidence: 99%
“…Homodimeric myosins are also preferentially formed in invertebrates such as Caenorhabditis elegans ( Miller et al, 1983 ) and in vertebrate skeletal muscles, where different developmental heavy chain isoforms are the products of separate genes in the multinucleated cells ( Lowey et al, 1991 ). When bacterially expressed LMM fragments of the adult and neonatal isoforms were denatured and renatured in vitro, they preferentially formed homodimers, indicating that the information for skeletal myosin formation probably is inherent in the amino acid sequence ( Arrizubieta and Bandman, 1999 ). In contrast, mammalian cardiac muscle contains amounts of heterodimeric V2 myosin comparable to those of the homodimeric V1 and V3 forms during certain stages of development ( Hoh et al, 1978 ; Lompre et al, 1979 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ni-NTA Column Chromatography. The use of Ni-NTA column chromatography to separate homodimers and heterodimers on the basis of the different affinity of zero, one, or two histidine-tagged LMM molecules for the Ni-NTA resin has been established before (29). A similar approach was taken here to study the amount of heterodimers or homodimers formed during the exchange experiments with His-tagged and FLAG-tagged or untagged MyHC rod.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the amount of homodimers and heterodimers was determined. The results indicated that neonatal and adult LMMs preferentially formed homodimers but ∼25% of heterodimers were also detected (29). However, in another study using chymotryptic full-length rods the amount of heterodimers formed was significantly less (9).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The ACD allows the tails of myosin dimers to self-assemble into antiparallel arrays that form the centre H-band of the thick filament. Filaments are rarely composed of only one form of type II myosin and often differences in the distribution of myosins within the thick filament are a result of subtle yet unidentified sequence differences in the tail domain [ 32 , 33 ]. For example, nematode body wall muscle thick filaments are composed of two different myosin heavy chains (MHC), A and B [ 34 ].…”
Section: Myosin Assemblymentioning
confidence: 99%